Vancomycin Serum Concentration after 48 h of Administration: A 3-Years Survey in an Intensive Care Unit - Nicolas Perin; Claire Roger; Grégory Marin; Nicolas Molinari; Alexandre Evrard; Jean-Philippe Lavigne; Saber Barbar; Pierre Géraud Claret; Caroline Boutin; Laurent Muller; Jeffrey Lipman; Jean-Yves Lefrant; et al. (MDPI AG, 2020)
The present study assessed the proportion of intensive care unit (ICU) patients who had a vancomycin serum concentration between 20 and 25 mg/L after 24-48 h of intravenous vancomycin administration. From 2016 to 2018, adult ICU patients with vancomycin continuous infusion (CI) for any indication were included. The primary outcome was the proportion of patients with a first-available vancomycin serum concentration between 20-25 mg/L at 24 h (D2) or 48 h (D3). Of 3894 admitted ICU patients, 179 were included. A median loading dose of 15.6 (interquartile range (IQR) = (12.5-20.8) mg/kg) was given in 151/179 patients (84%). The median daily doses of vancomycin infusion for D1 and D2 were 2000 [(IQR (1600-2000)) and 2000 (IQR (2000-2500)) mg/d], respectively. The median duration of treatment was 4 (2-7) days. At D2 or D3, the median value of first serum vancomycin concentration was 19.8 (IQR (16.0-25.1)) with serum vancomycin concentration between 20-25 mg/L reported in 43 patients (24%). Time spent in the ICU before vancomycin initiation was the only risk factor of non-therapeutic concentration at D2 or D3. Acute kidney injury occurred significantly more when vancomycin concentration was supra therapeutic at D2 or D3. At D28, 44 (26%) patients had died. These results emphasize the need of appropriate loading dose and regular monitoring to improve vancomycin efficacy and avoid renal toxicity.